Role of Alvarado score in the diagnosis of acute appendicitis - G, Vijay Bhaskar Reddy; VV, Subramanyam; B, Veersalingam; Sateesh, Sreeram; Bangla, Gidion; Rao, Pasupuleti Sreenivasa (International Journal of Research in Medical Sciences, 2017)
Acute appendicitis is a surgical emergency, which is associated with morbidity and mortality occasionally. If failed to diagnose early the situation may become more complicated. In acute appendicitis it is not possible to have definitive diagnosis by histopathology preoperatively, we would like a simple test like Alvarado scoring system which depends on the presence and absence of certain variable, which provides an accurate guide to whether or not the patient has the condition. Hence, accurate diagnosis and timely intervention is needed. Therefore, the present study was conducted to evaluate the Alvarado scoring system in diagnosing acute appendicitis and its co relation with histopathology. This prospective study was conducted in 100 consecutive patients admitted in the department of general surgery of Narayana Medical College, Nellore with the clinical diagnosis of acute appendicitis. The findings based on the Alvarado score indicate that 68% of the subjects had a score of more than 7 and 22% of the subjects had a score between 5 and 7. Only 10% of the subjects had a score between 1 and 4. Out of 83 eligible subjects 75 were found to have acute appendicitis by histopathological examination. Negative appendicectomy was very low representing up to 9.6% whereas the percentage of positive predictive value was high representing up to 90.4%. Although the diagnosis of acute appendicitis remains mainly clinical evaluation, the scoring system is easy, simple and cheap complementary aid for supporting the diagnosis of acute appendicitis.